A preliminary validation of PMQ—A four-factor questionnaire measuring parental mentalizing - Teräsahjo, Timo; Turunen, Tiina; Lahtinen, Oskari; Salmivalli, Christina (Frontiers in Psychology, 2024)
The present study describes the construction and preliminary validation of a new parental mentalizing scale, PMQ. Based on theory, we hypothesized that one higher-order parental mentalizing factor would comprise four dimensions of parental mentalizing: (1) Parental self-mentalizing (SELF), (2) Parental child-mentalizing (CHILD), (3) Effort (E), and (4) Curiosity (C). After modifying the content of one factor (Effort > Lack of Effort, LE), four-factor structure with one higher-order factor was confirmed in data collected from parents of children aged two to 6 years through social media and email lists (N = 321, 10% male). All factors loaded significantly on the higher-order factor, with acceptable internal consistencies. Next, PMQ factors were compared with the factors of a previously validated questionnaire, parental reflective functioning questionnaire (PRFQ). The PMQ and PRFQ factors were consistently and significantly correlated, indicating the validity of the PMQ as a measure of parental mentalization ability. The continuation of PMQ validation is discussed.